2006
DOI: 10.1590/s0036-46652006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors for toxocariasis in children from a pediatric outpatient center in southeastern Brazil

Abstract: SUMMARYTo estimate the frequency of anti-Toxocara sp. antibodies, and evaluate factors associated with this infection, sera from 242 male and female children, aged from one to fifteen years old, attended at the Hospital of the Federal University of Uberlândia, Minas Gerais State, Brazil, were analyzed by ELISA. Information on the patients was collected and registered using an investigative questionnaire, and details on possible clinical alterations were obtained from the medical charts of 187 patients. Of a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
2
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 34 publications
8
23
2
15
Order By: Relevance
“…On the other hand TEIXEIRA et al (2006) 32 found a correlation between positive serology, respiratory symptoms, and eosinophilia. This is explainable, because the clinical aspects of toxocariasis can vary from asymptomatic forms to pulmonary, ocular, and hepatic clinical pictures, among others.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand TEIXEIRA et al (2006) 32 found a correlation between positive serology, respiratory symptoms, and eosinophilia. This is explainable, because the clinical aspects of toxocariasis can vary from asymptomatic forms to pulmonary, ocular, and hepatic clinical pictures, among others.…”
Section: Discussionmentioning
confidence: 94%
“…This means that children and adolescents of both genders are exposed to the same kind of toys and the same recreational environments. Data on these epidemiological factors are controversial in different study areas 4 32 observed an association between seropositivity and the presence of a dog or cat, and presence of sand at school. In the present study, the school places were more contaminated than the squares, highlighting the risk to children and adolescents in their school activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ownership of pets such as dogs or cats and their presence at home is frequently associated with toxocariasis, as mentioned by many authors 5,22,24,28,[34][35][36][37] . However, this fact was not associated with the seropositivity in the studied population (p = 0.107).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, few comparable data are currently available for rural areas, where human infections are usually most prevalent. 11 Seropositivity rates between 8.7% and 39.0% have been found in different samples of Brazilian children (sample size, 100-483) examined over the past decade, [12][13][14][15][16][17][18] but exposure to Toxocara has been rarely investigated in other age groups and no data are available for rural populations of this country. 19 Here we describe the epidemiology of human toxocariasis in one of the largest agricultural settlements in the Amazon Basin of Brazil, the Pedro Peixoto settlement in the state of Acre.…”
Section: Introductionmentioning
confidence: 99%